Induction of autotetraploid Moringa plant (Moringa oleifera) using oryzalin - Ridwan Ridwan; Witjaksono Witjaksono (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Ridwan, Witjaksono. 2020. Induction of autotetraploid Moringa plant (Moringa oleifera) using oryzalin. Biodiversitas 21: 4086-4093. Moringa (Moringa oleifera Lam.) is a plant with high nutritional content and has been widely used as a vegetable and health food ingredient, but its utilization and productivity have not been optimal. Increasing plant productivity can be done by increasing biomass which can be obtained through increasing plant ploidy. This study aims at obtaining tetraploid Moringa by induction using oryzalin compound. Moringa germinating seeds were soaked in oryzalin water solutions for 1, 3, and 5 days with concentrations of 0 µM (control), 15 µM, 30 µM, 60 µM, and 120 µM with 10 seeds for each treatment. We have recovered two tetraploid Moringa plants and two chimeric plants of diploid and tetraploid genomes. Immersing germinating seeds for 1 day in 15 or 60 µM oryzalin concentration effectively induced autopolyploid in Moringa. Tetraploid plants exhibit typical morphological characteristics of a tetraploid, such as low stomata density, larger stomata size, and larger leaflet size compared to the diploid counterpart. The induced tetraploid plants have significantly increased protein, fat, and calcium content compared to the diploid counterpart emphasizing their values as functional food. This polyploidy induction method can be used to produce Moringa tetraploid lines from various accessions in the attempts of developing and selecting high yielding tetraploid Moringa cultivars.